Vehicle Volume And Carbon Monoxide And Nitrogen Oxide Emissions On Weekdays And Weekends On Anggajaya Street, Sleman - Nirmalasari, Novi; Satriani, Narendra (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2025)
Anggajaya Road, located in Condongcatur Village, Depok Subdistrict, Sleman Regency, is directly connected to the Ring Road Utara Road and serves as a residential area with boarding houses, shops, and terminal.This study aims to determine the traffic volume and exhaust emissions of carbon monoxide and nitrogen oxide gases on Anggajaya Road, Sleman Regency. The research method employed was observational, conducted during weekends and weekdays from 09.00-11.00 WIB. The observed types of vehicles include motorcycles, cars, trucks, and buses. The result was that the vehicle volume was 0,335 smp per second on weekend and 0,277 smp per second on weekday. The emission levels of carbon monoxide and nitrogen oxide were higher during the weekend compared to weekday.